Characteristics and controlling factors of tectonic fractures within the buried hill reservoirs from the Archaean metamorphic basement: a case study in the Bozhong 19–6 condensate gas field, Bohai Bay Basin - Liu, Zongbing; Cheng, Qi; Liao, Xinwu; Zhang, Lei; Liu, Wenchao; Zhang, Guanjie (Frontiers in Energy Research, 2024)
The Bozhong 19–6 Condensate gas field is the first giant gas field discovered in the Bohai Bay Basin in recent years. The gas field reservoir has diverse reservoir space and strong heterogeneity.In this paper, we systematically summarize tectonic fractures development patterns and explore the main factors controlling fractures development and clarify the influence of fractures on reservoir quality through core and microscopic thin section observations, physical property data, imaging logging data. The results show that the major types of tectonic fractures in study area are shear fractures, followed by tensile fractures. Study area mainly developed high-angle fractures and completely filled fractures, fractures are commonly filled with carbonate and clay cement. Four groups of tectonic fractures were found in the study area, which corresponds to the four fracture formation period. Tectonic movement controls the fractures development in study area, the multi-stage tectonic movement had caused a complex fractures network system. The faults control the development of associated fractures formation in the fractures zone, different faults control the fractures formation and orientations in the vicinity. Rock type and minrals content is the basis of forming different fractures, such as the high felsic content is the basis of developed fractures in metamorphic rocks, and rock layer thickness, reservoir porosity and permeability are important factors of the fractures development heterogeneity longitudinally.